Outcomes of Selective Laser Trabeculoplasty as Primary Treatment for Ocular Hypertension and Mild Open Angle Glaucoma in the Saudi Arabian Population - Almarzouki, Nawaf (Journal of Contemporary Medical Sciences, 2024)
Background: Selective laser trabeculoplasty (SLT) is a promising, minimally invasive, non-surgical procedure for lowering IOP in glaucoma patients. While various studies have established the efficacy of SLT in lowering IOP in glaucoma patients there are limited data on its outcomes as a primary treatment modality in the Saudi Arabian population. That’s why it is essential to understand the effectiveness of therapeutic interventions in specific populations to optimize treatment strategies. Methods:. A retrospective cohort design was used. 54 eyes of patients with ocular hypertension (OHT) or mild primary open-angle glaucoma (POAG) underwent SLT. IOP, medication use, and potential influencing factors were monitored over one year. Results: SLT significantly reduced IOP (p < 0.001 for all comparisons). The mean IOP decreased from 20.57 mmHg at baseline to 14.72 mmHg at one month (a 28.4% reduction) and remained substantially low during the year (15.39 mmHg at six months and 15.44 mmHg at one year). After SLT, the proportion of eyes achieving well-controlled IOP (<21 mmHg) significantly increased from 51.9% at baseline to 96.3% at one year (p < 0.001). This improvement was observed across all patient subgroups, including those with OHT, mild POAG, normal-tension glaucoma, and secondary glaucomas. Before SLT, all patients were medication-free. At one year, 74.1% remained medication-free, while 25.9% required one medication (p < 0.001). Greater IOP reduction was associated with a longer time since SLT, younger age, and diagnoses of mild POAG or normal tension glaucoma (all p < 0.05). Conclusion: SLT demonstrated significant and sustained IOP reduction in the Saudi Arabian population with OHT and mild POAG. It also led to a substantial decrease in medication use. These findings suggest SLT as a viable primary treatment option for this patient population, though further research is needed to explore long-term outcomes.